Economics of production and marketing of wheat in Rupandehi district of Nepal - Kharel, Meena; Ghimire, Yuga Nath; Timsina, Krishna Prasad; Adhikari, Surya Prasad; Subedi, Sanjiv; Poudel, Hema Kumari (Journal of Agriculture and Natural Resources, 2021)
Wheat is the third most important cereal crop of Nepal after rice and maize in terms of area. The study on profitability and marketing of wheat was conducted in the Rupandehi district in 2019. The household survey, focus group discussion, interview with the individual market actors such as input suppliers, producers, collectors, wholesalers, millers, and retailers in selected clusters was carried out. The study showed that the Benefit-Cost Ratio of wheat production (BCR) was 1.87. The marketing margins at three different levels of marketing farm-wholesale, wholesale-retail, and farm-retail were also analyzed. The farm-retail marketing margin was found highest (31.42%) and the farm-wholesale marketing margins were less (15.78%). The producers’ share in consumer price was 68.5% and the total gross margin was 56.36%. This showed if value-added activities are absent in the chain, the shorter chain can provide a higher margin to farmers by bypassing the intermediaries.